Dinamika Gaya Kepemimpinan dalam Strategi Optimalisasi Penguatan Kinerja Karyawan Studi Empiris pada Perusahaan LQ45 Periode 2022–2023 - Satrio Ahmadtul Firdaus Romadhoni; Abdul Hamid Syarif; Sopiah Sopiah (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
In the era of globalization and increasing intensity of competition, public companies in Indonesia are required to develop internal strategies that are able to support sustainability and performance improvement in a sustainable manner. This study aims to analyze the relationship between leadership style, work discipline, and compliance with the principles of good corporate governance (GCG) in companies that are members of the LQ45 index on the Indonesia Stock Exchange. The method used is a normative qualitative approach with document study techniques, using secondary data in the form of annual reports, sustainability reports, and related academic literature. The results show that the application of transformational leadership styles, characterized by employee empowerment, innovation, and sustainable motivation, is significantly positively correlated with the implementation of a structured work discipline system and adherence to GCG principles. These findings confirm that the integration between effective leadership and organizational discipline is a strategic foundation in creating an adaptive, competitive, and integrity work culture. This research makes an important contribution to strengthening contemporary management theory and corporate governance practices, as well as becoming a reference for companies in building a superior internal management system.